“A Fisheye View of Aquatic Education in Louisiana” - Lindsay Seely (Current: The Journal of Marine Education, 2025)
The Louisiana Department of Wildlife and Fisheries (LDWF) Aquatic Outreach and Education section is tasked with educating multiple audiences of different age ranges on various fisheries-related topics throughout the state. The section oversees several programs which cater to the general public, educators, and students. This article serves to showcase the goals and overall impacts of the section, providing a big picture—or fisheye—view of the programs that the LDWF Aquatic Outreach and Education section have found to enhance aquatic education around the state of Louisiana.